Mushthalaẖât Al-Hâsib Al-Âlî Wa Al-Istifâdah Minhâ Fî Itsrâ`i Al-Lughah Al-`Arabiyyah Ladâ Al-Muta`allimîn Ghairi An-Nathiqin Biha - Hilmayasin; Sa`adiyah Ratnasari Sagala (Mauriduna: Journal of Islamic Studies, 2021)
إن المصطلحات لها دور وسيم في ترقية المستوى اللغوي لمتعلمي اللغة خاصةً غير الناطقين بها. والمعرفة عنها تساعد متعلمي اللغة الحصول على الكفاية والكفاءة اللغوية. فهدفت هذه الدراسة إلى معرفة مصطلحات الحاسب الآلي المختارة الشائعة ومعانيها، وإلى معرفة كيفية الاستفادة منها في إثراء اللغة العربية. وهذه الدراسة هي البحث الكيفي تسلك المنهج الوصفي التحليلي. وهنك ثلاث مراحل لإجراءات البحث الكيفي وهي جمع البيانات، وعرض البيانات، والاستنتاج. وهذه المراحل تكون دليلاً للباحثة في جمع البيانات المتعلقة بموضوع الدراسة، والبحث عن المصطلحات الشائعة من عدة معاجم وترتيبها وعرضها والاستفادة منها. وأثبتت الدراسة النتائج بعد جمع المصطلحات، بحيث بلغ عددها 230 مصطلحًا وتحتوي على 3 أقسام وهي: القسم الأول: القائمة عن المصطلحات دلت على أفعال أو عملية ما، والقسم الثاني: القائمة عن أسماء الآلات والأجهزة، والقسم الأخير: المصطلحات في نظام الحاسب الآلي والبرنامج الحاسوبي. وتم طرق الاستفادة منها في إثراء اللغة العربية لدى المتعلمين غير الناطقين بها بوضعها في نصوص القراءة، وتصميم صياغة الحوارات، والألعاب اللغوية. Scientific terms have an important role in increasing the ability of foreign languages, especially for the students who are non- native speakers. The knowledge in the terms of field of science can help students in gaining linguistic intelligence. Therefore, this research is intended to look for general terms in the field of Computer Science and their meaning, and then find the applicable applicative theories that are suitable for improving Arabic language skills. This research is a Qualitative Research using Descriptive – Analysis Method, where the research is conducted in 3 stages: data reduction, data classification, data exposure and data conclusions. Referring from this method, the Researcher looks for data related to the scope of the study, then collects general terms from several dictionaries, then explains them and uses them to improve Arabic linguistic abilities. The results of the study were concluded after the Researcher collected data on general computer terms, then 230 terms were collected. The division is divided into 3 categories. First: the term computer equipment and machines, second: the verb term in computer operations, third: the term system and computer program. Furthermore, these terms are applied in the form of narration, dialogue, and games in an effort to improve Arabic language skills among foreign students.